EFFECT STUDY OF WOOD STRENGTH CLASSES ON JOINING SYSTEM IN FURNITURE DESIG - Agung Syaputra, Eko
Wood furniture products are one of the strategic commodities that have a dominant contribution compared to other material furniture for the Indonesian economy. The type of wood utilized by the timber industry is the result of natural production forests which cover half the area of tropical forests. The total area of tropical forests covers 126.09 million hectares. This type of wood is referred to as the common used species. At present the amount of supply of trade wood species that can be harvested from natural production forests is decreasing, so that it has an impact on the timber industry that has begun to utilize wood species with a large enough volume but their use is still not optimal (lesser used species). Wood is classified into five types of strength classes which are determined based on specific gravity, absolute curvilinear firmness, and absolute compressive firmness. As a production material, the strong type of wood can determine the mechanical quality of the furniture produced. In addition, another aspect of furniture design is the joining system which will affect the mechanical quality of the product. In the application of the joining system depends on the form of furniture and the type of wood used. The purpose of this study is to identify the relationship between strong wood classes and the joining system to furniture design. This research uses qualitative and quantitative methods. This method was chosen to understand the issue or research problem by triangulating qualitative data in the form of descriptive details with qualitative data in the form of numbers, so as to produce more comprehensive and valid data. This research is expected to be a reference in the process of designing wood furniture so that it can produce furniture that has a match between the shape, material, and joining system.